Ответ:
-3,15
Пошаговое объяснение:
4,2(0,4х -1) - (2,68х - 1,8) при х = 0,75
4,2 * (0,4х -1) - (2,68х - 1,8) = 4,2*(0,4*0,75 - 1) - (2,68*0,75 - 1,8) =
4,2*(0,3 - 1) - (2,01 - 1,8) = 4,2*(-0,7) - 0,21 = -2,94 - 0,21 = -3,15
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-3,15
Пошаговое объяснение:
4,2(0,4х -1) - (2,68х - 1,8) при х = 0,75
4,2 * (0,4х -1) - (2,68х - 1,8) = 4,2*(0,4*0,75 - 1) - (2,68*0,75 - 1,8) =
4,2*(0,3 - 1) - (2,01 - 1,8) = 4,2*(-0,7) - 0,21 = -2,94 - 0,21 = -3,15